COME: cost optimisation with multi-chaining for energy efficient communication in wireless sensor networks. (2015) - Ahmad, Ashfaq; Javaid, Nadeem; Ahmed, Syed Hassan; Bouk, Safdar Hussain; Ilahi, Manzoor; Kim, Dongkyun
In this paper, we present two new chain formation techniques, namely, multi-chain energy efficient routing (ME) and cost optimisation with multi-chaining for energy efficient communication (COME) for wireless sensor networks supported by linear programming based mathematical models. ME protocol divides network area into subareas of equal size, which contain equal number of randomly deployed nodes. Furthermore, minimum distance based next hop for data transmission is used and the sojourn locations are adjusted in a way that, at a time when data reaches to the last node of the chain (terminator node), BS moves to the possible nearest location of that node (sojourn location). ME uses shorter routes for communication. COME protocol closely inspects the energy costs and selects route with minimum energy cost. Simulations show improved results for our proposed protocols as compared to PEGASIS in terms of the stability period, network lifetime, dropped packets and throughput.